Microwave assisted green synthesis of ZnO nanotubes using Amorphophallus paeoniifolius tuber extract. Issue 1 (February 2021) - Naresh Kumar, P; Vijayakumar, B; Ranjith, R
Abstract: Green nanoparticle synthesis is gaining significant interest and is the perfect alternative to the chemical and physical synthesis process. This paper introduces a novel plant-mediated microwave-assisted green synthesis of Zinc Oxide (ZnO) nanotubes using Amorphophallus paeoniifolius tuber extract. In the nanoparticle synthesis process, the tubers phytochemicals serve as a reducing agent and a bio template. The synthesized nanoparticles are exposed to microwave radiation for 15 minutes and are then annealed at 400°C for 1 hour. The green synthesized nanoparticles are analyzed with XRD, UV-Vis spectroscopy, HRTEM, EDX, and FTIR spectroscopy. Subsequently, TEM images depicts the tube-shaped ZnO NPs with d-spacing of 2.3Å. The XRD confirms the wurtzite phase with 14 nm as mean particle size.